Bimbingan Konseling Dalam Perspektif Pendidikan Islam - Iqbal Amar Muzaki; Amirudin Amirudin; Siti Sukma Rianti (UMSU, 2022)
This article discusses guidance and counseling in an Islamic perspective. This research method is a literature study, which is done by searching, collecting, reading, taking notes on the sub-discussions in Islamic guidance and counseling. The data collection technique in this research is library research, namely data collection activities related to research obtained from books, scientific journals, literature and other publications that are used as references for research researched by the author. The purpose of this study is to find out counseling guidance in an Islamic perspective, not only the meaning of counseling guidance in Islam, but also to explain the purpose, function, therapy in Islam and the requirements of a counselor in Islam. Many already know about the purpose and function of counseling guidance in general, but do not fully understand it Islamically. Especially at times like this that limit meetings, activities that make anxiety or worry increase. So, we explain how to deal with anxiety easily and without the need to visit a specialist or a psychiatrist. If the anxiety level is too high, it is possible to visit a specialist or a counselor. An Islamic counselor must have criteria according to the Islamic perspective. With this journal, it is hoped that it will make it easier for readers to understand counseling guidance in the perception of Islam as well as reminding each other to worship so as to reduce anxiety or worries about life.